Pengaruh Tingkat Pengangguran dan Kesehatan terhadap Indeks Pembangunan Manusia di Provinsi Lampung 2020-2023 - Imelda Deva Kirana; Amanda Aulia; Devika Putriani; Misfi Laili Rohmi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the effect of unemployment rate and health on the Human Development Index (HDI) in Lampung. This study uses a quantitative method with multiple regression analysis to test the effect of independent variables (unemployment rate and health) on the dependent variable (HDI). The results of the study indicate that the unemployment rate has a significant positive effect on the HDI, where an increase in unemployment has the potential to increase the HDI figure. On the other hand, the health variable does not show a significant effect on the HDI, indicating that although the health program is running, other factors such as the economy and education are more dominant in determining the HDI. Simultaneously, unemployment and health contribute to changes in the HDI, but the dominance of unemployment appears stronger.